APPLICATION OF CORRELATION ANALYSIS FOR ASSESSMENT OF AGE EXPERIMENTAL NEPROTOXICITY OF OXALATES - Andriy, Mikheev (Sworld-Us Conference proceedings, 2023)
The article shows the peculiarities of the localization of disturbances in the tubular transport of sodium ions under conditions of experimental hyperoxaluria with the use of correlation analysis of the main parameters of the functional state of the kidne